STUDY OF SMART AND SUSTAINABLE CREATIVE CITY (CASE STUDY: BANDUNG CITY) - Ekaputra, Diaz
The rapid growth of cities requires strategic steps to increase competitiveness. City Branding is one of the strategies to achieve this, so every city needs to define its uniqueness as an attraction. The city of Bandung has an inherent brand, such as a creative city of design that UNESCO and a smart city have recognized. On the other hand, the Indonesian government is pushing for sustainable urban development to achieve the 2030 Agenda. There are many criticisms of the concept of smart cities that are outside of sustainable development, so the contribution of smart cities in achieving sustainable development is essential. The study results show that the city of Bandung still needs to implement the smart and sustainable creative city concept. The level of readiness is also unevenly distributed in every sub-region in the city of Bandung. In encouraging smart, creative cities that are also sustainable, this study reveals that the aspects that need to be encouraged to realize these goals are aspects of planning, history, accessibility, creative space, safety, economic sustainability, waste, collaboration actors, use of technology, facilities and infrastructure, and innovation creation. Therefore, to optimize the readiness of smart and sustainable creative cities in Bandung, the uniqueness of each sub-region needs to be considered in developing cities, and the government needs to provide a solid commitment to its development.